A novel nonlinear controller for enhancement of the transient dynamics performance of a three-wheeled vehicle during different conditions. (December 2021) - Saeedi, Mohammad Amin
In this study, a new controller to prevent the yaw instability and rollover of a three-wheeled vehicle has been proposed. This controller offers the most obvious opportunity for affecting the vehicle's lateral dynamics performance on the full range of nonlinearities during various operating boundaries. The active combined controller has been designed based on sliding mode control method using an active roll system and an active braking system to dominate the uncertainties of the nonlinear dynamic model. Firstly, to avoid rollover of the three-wheeled vehicle, the roll angle was considered as the control objective, and the anti-roll bar was employed as an actuator to produce the roll moment. Secondly, to increase the maneuverability and lateral dynamics enhancement, an active braking system was designed. In the control system, the yaw rate and the lateral velocity were regarded as the control variables to track their references. Moreover, to verify the performance of the mentioned combined controller, another control system has been designed using the linearization feedback control method. Then, computer simulation has been carried out with a 12 degrees of freedom dynamic model of the three-wheeled vehicle called the delta. Furthermore, a nonlinear tire model has been utilized to compute the longitudinal and the lateral forces. Next, the comparative simulation results confirmed the effectiveness of the robust control system to raise the vehicle's maneuverability and its rollover stability in comparison with the linearization feedback control method, especially when the three-wheeled vehicle is subjected to critical conditions.